The influences the tangible and intangible cultural heritage in formulating the Architectural language Case study: The Heritage city of GeorgeTown, Penang- Malaysia - Mohammed, Zinah S.; Bahauddin, Azizi (Sulaimani Journal for Engineering Sciences, 2019)
The identity of the heritage space perceived by the visitor depending on the tangible and intangible elements, which is influenced by the cultural values. The sense of place is the generator of the cultural heritage space. The physical elements of the space in the street have the role in the activating the identity. GeorgeTown is the heritage city of the northern state of Penang Island in Malaysia, which listed in the World Heritage Site (WHS) by the UNESCO in July 2008. GeorgeTown well known as a colorful culture place, which attracts millions of tourists yearly. The contemporary needs of the city as a host of foreign and local visitors create type of shifting on the identity of the place. The architectural elements of the facades started to lose the authenticity of the heritage value during the rehabilitation, reconstruction, and new construction processes. The problem of the current study observed from site as urgent needs to establish a standard of creating physical cultural heritage space du the waves of changing in the original characteristics of the physical elements in the street. The study obtained a research question, which are, “what is the architectural language of the cultural heritage space, which can enhance the cultural heritage image of the GeorgeTown”. Therefore, the study aim is to find the components and the rules of this language. However, Beach Street selected as a case study, which is one of the most important heritage trails in Georgetown. The study used qualitative approach, using visual observation and in-depth interview with experts and pedestrians. In the current study used formal, content, and phenomena analysis techniques. The results show, that the architectural language included two systems, formulating and influences systems. The results of the study presented as a model of the architectural language, which contained the architectural elements, principles, and relationship. While, the influence system included the architectural style, symbols, and elements. The architectural language in the heritage cities has a rule in the conserving the cultural heritage space.
Keywords: Culture influences; Façade elements; architectural language